The Relationship between Job Stress, Toxic Environment Workplace and Job Performance - Suwito, Nurul Aliah Nadia; Nasuredin, Juzaimi (Research in Management of Technology and Business, 2025)
Workplace stress and toxic environments are serious issues that can negatively impact employee performance and organizational productivity. However, the extent to which these factors influence job performance in Malaysia's private sector remains underexplored. This study addresses the need to understand how job stress and toxic workplace environments affect employee performance in the private sector of Johor. Using a quantitative approach, data were collected from 224 respondents through structured questionnaires. The study employed reliability testing, descriptive analysis, and Spearman correlation to analyze relationships among job stress, toxic environments, and job performance. Reliability assessments demonstrated acceptable internal consistency for the Job Stress Questionnaire, Toxic Environment Workplace Questionnaire, and Job Performance Questionnaire, with Cronbach's Alpha values of 0.74, 0.86, and 0.74, respectively. The findings revealed a weak positive correlation between job stress and job performance, suggesting that moderate levels of stress can stimulate productivity. Similarly, a minimal positive relationship between toxic workplace environments and job performance indicates that employees may adapt to adverse conditions to maintain productivity. Nonetheless, these effects are limited, underscoring the importance of addressing workplace stressors and environmental toxicity. This study highlights the critical need for organizations to implement measures that reduce stress and toxicity, ensuring employee well-being and sustained productivity. It also emphasizes the potential of organizational culture and leadership as additional factors influencing job performance. Future research should explore these dimensions to provide a holistic understanding of workplace dynamics.